Economic Evaluation of Infliximab for Treatment of Refractory Ulcerative Colitis in Iran: Cost-Effectiveness Analysis: Economic Evaluation of Infliximab in UC Patients - Najmeh Moradi,; Leila Zarei,; Shahram Tofighi,; Marzieh Zanganeh,; Ali Akbari Sari, (Iranian Journal of Pharmaceutical Sciences, 2016)
The aim of this study is to assess cost-effectiveness of infliximab, compared with conventional treatments in patients with moderate to severe Ulcerative Colitis (UC) in Iran. We developed an analytical decision model with a 5-year-time horizon to follow up 1000 hypothetical patients, in order to estimate treatment costs and outcomes. Hypothetical patients were individuals with moderate to severe UC that are resistant to conventional treatments. Remission rate, clinical response, and surgery were selected as clinical outcomes. For estimating QALY, utility value related to each state, was derived form published paper. We also estimated associated probabilities by using patients ’medical records and specialists’ opinion. Costs of treatment such as Physician visit fee, laboratory tests, hospitalizations, surgery, and drugs were estimated based on the public sector tariffs and drug price list set by pricing committee of food and drug administration. Infliximab costs at dosage of 5 mg /kg were considered for UC patients with average weight of 75 kilogram. Incremental Cost-Effectiveness Ratio (ICER) of infliximab treatment in UC patients were 240,903 USD dollars per QALY gained, compared with conventional treatments. According to recommendation of World Health Organization for choosing cost-effective intervention, interventions with relative cost-effectiveness value less than 3 times of Gross Domestic Production (GDP) per capita, are cost–effective. Our result showed that the ICER value of infliximab is approximately 51 times of Iran’s local GDP per capita, in 2014 – i.e. more than 3 time GDP per capita. Thus, for UC patients, our finding indicates that infliximab is not a cost- effective treatment.